2019
DOI: 10.1021/acsanm.9b00640
|View full text |Cite
|
Sign up to set email alerts
|

Patterned Cellulose Nanocrystal Aerogel Films with Tunable Dimensions and Morphologies as Ultra-Porous Scaffolds for Cell Culture

Abstract: Aerogel films are interesting as coatings due to their unique properties including high surface area, sorption capacity and insulating properties. To date, silica-based aerogel films have been most widely explored due to their ultrahigh surface areas and well-known chemistry. However, the fragile nature of silica aerogels coupled with the limited control over film thickness and dimensions when using traditional deposition techniques limits their use in applications requiring films with good mechanical stabilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 45 publications
0
25
0
Order By: Relevance
“…Aerogel films (1 wt % sol–gel concentration, 1:1 aCNC:hPOEGMA weight ratio) were patterned onto the counter electrodes by using a recently developed pressure-aided freeze casting technique. 40 Briefly, FTO-coated glass was cleaned with piranha solution (5:1 H 2 SO 4 :H 2 O 2 v/v) for 15 min at 110 °C while ITO-coated PET was cleaned by using UV-ozone (Novascane, Boone, IA) for 2 h to remove organic residue. A 20 nm thick catalytic Pt layer was sputtered onto the counter electrodes by using a Torr Compact Research Coater CRC-600 manual planar magnetron sputtering system (Torr International, New Window, NY).…”
Section: Methodsmentioning
confidence: 99%
“…Aerogel films (1 wt % sol–gel concentration, 1:1 aCNC:hPOEGMA weight ratio) were patterned onto the counter electrodes by using a recently developed pressure-aided freeze casting technique. 40 Briefly, FTO-coated glass was cleaned with piranha solution (5:1 H 2 SO 4 :H 2 O 2 v/v) for 15 min at 110 °C while ITO-coated PET was cleaned by using UV-ozone (Novascane, Boone, IA) for 2 h to remove organic residue. A 20 nm thick catalytic Pt layer was sputtered onto the counter electrodes by using a Torr Compact Research Coater CRC-600 manual planar magnetron sputtering system (Torr International, New Window, NY).…”
Section: Methodsmentioning
confidence: 99%
“…44,46,47 Cellulose and its derivatives', specifically CNCs, mechanical properties improve stiffness and strength of polymer composites promoting the creation of novel polymer nanocomposites and lubricants 48,49 or improving shape memory effects of polymer matrices. 50 In addition to synthetic polymers, chemically modified cellulose derivatives such as cellulose acetate, hydroxypropyl cellulose, and carboxymethyl cellulose have been used as additives for functional biomaterials to create films, membranes, electrospun into nanofibers 51 as well as formed into aerogel films, 52 hydrogels, 53 and three-dimensional porous foams. 54,55,56,57 Fernandes et al presented several studies that showed cellulose and its derivatives are biocompatible and have tunable biodegradable properties.…”
Section: Introductionmentioning
confidence: 99%
“…Aerogels are ultra-low-density [33], dry, and very porous monolithic materials [34] taken from a gel composed of nanoparticles or polymers that chemically or physically cross-linked to a three-dimensional network [35]. Typically there are two stages for the synthesis of these materials, which are, rst, the formation of wet-gels through the process of sol-gel [36], and then drying the obtained gels using a method that keeps the internal porous morphology as possible [35] [37]. The aerogel, rst synthesized in the late 1930s by Kistler [38], can be inorganic [39], organic [40], and hybrid [41] aerogels according to their composition [42].…”
Section: Introductionmentioning
confidence: 99%